T2* Placental Magnetic Resonance Imaging in Preterm Preeclampsia: An Observational Cohort Study. Issue 6 (June 2020) - Ho, Alison E.P.; Hutter, Jana; Jackson, Laurence H.; Seed, Paul T.; Mccabe, Laura; Al-Adnani, Mudher; Marnerides, Andreas; George, Simi; Story, Lisa; Hajnal, Joseph V.; Rutherford, Mary A.; Chappell, Lucy C.
Abstract : Placental dysfunction underlies the cause of pregnancies complicated by preeclampsia. The use of placental magnetic resonance imaging to provide an insight into the pathophysiology of preeclampsia and thus assess its potential use to inform prognosis and clinical management was explored. In this prospective observational cohort study, 14 women with preterm preeclampsia and 48 gestation-matched controls using 3-Tesla magnetic resonance imaging at median of 31.6 weeks (interquartile range [IQR], 28.6–34.6) and 32.2 weeks (IQR, 28.6–33.8), respectively, were imaged. The acquired data included T2-weighted images and T2* maps of the placenta, the latter an indicative measure of placental oxygenation. Placentae in women with preeclampsia demonstrated advanced lobulation, varied lobule sizes, high granularity, and substantial areas of low-signal intensity on T2-weighted imaging, with reduced entire placental mean T2* values for gestational age (2 sample t test, t=7.49) correlating with a reduction in maternal PlGF (placental growth factor) concentrations (Spearman rank correlation coefficient 0.76) and increased lacunarity values (t=3.26). Median mean T2* reduced from 67 ms (IQR, 54–73) at 26.0 to 29.8 weeks' gestation to 38 ms (IQR, 28–40) at 34.0 to 37.9 weeks' gestation in the control group. In women with preeclampsia, median T2* was 23 ms (IQR, 20–23) at 26.0 to 29.8 weeks' gestation and remained low (22 ms [IQR, 20–26] at 34.0–37.8 weeks' gestation). Histological features of maternal vascular malperfusion were only found in placentae from women with preeclampsia. Placental volume did not differ between the control group and women with preeclampsia. Placental magnetic resonance imaging allows both objective quantification of placental function in vivo and elucidation of the complex mechanisms underlying preeclampsia development. Abstract : Supplemental Digital Content is available in the text.